2018
DOI: 10.1186/s12875-018-0818-2
|View full text |Cite
|
Sign up to set email alerts
|

What can family medicine providers learn about concussion non-disclosure from former collegiate athletes?

Abstract: BackgroundDespite the risks, concussion symptoms often go underreported by athletes, leading to delayed or forgone treatment and increased potential for concussion recurrence. One of the most serious long-term consequences of sports-related concussions is Chronic Traumatic Encephelopathy (CTE), a disorder associated with progressive neurological deterioration. The purpose of this study was to explore former collegiate athletes’ understanding of concussions and motivations behind concussion non-disclosure in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…al., 2021). Some of these barriers include players believing concussions are an inherent part of the game, a player's passion/competitiveness, withholding information from trainers and coaches, being embarrassed by receiving a concussion in a low-impact sport, team culture, and not understanding that concussions can occur in any/all sports (Beverly et. al., 2018).…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…al., 2021). Some of these barriers include players believing concussions are an inherent part of the game, a player's passion/competitiveness, withholding information from trainers and coaches, being embarrassed by receiving a concussion in a low-impact sport, team culture, and not understanding that concussions can occur in any/all sports (Beverly et. al., 2018).…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Self-reported symptoms are an important component of injury diagnosis, and previous studies have demonstrated that athletes may hide or underreport symptoms to avoid missing play time, especially with concussions. [19][20][21][22] Previous literature has demonstrated factors associated with nondisclosure as male sex, participation in a high-risk sport, and pressure from a coach to play after sustaining a hit. 23 Given that common motivations for nondisclosure are not wanting to leave the game or practice and not wanting to let the team down, the greater burden of responsibility to identify wrestling injuries may be borne by coaches, trainers, and parents.…”
Section: Discussionmentioning
confidence: 99%
“…Prior qualitative studies have explored student-athletes' education regarding concussion, past or present personal experiences of concussion, and support of concussed individuals as they return to school. From this work, it becomes very apparent that healthcare providers, coaches, athletic trainers, teachers, and parents should learn more about concussions, understand that they can occur in all sports, and recognize signs or symptoms of injury (18). The current study is consistent with, but adds to, this prior literature.…”
Section: Discussionmentioning
confidence: 99%